Interplay of Working Capital Turnover, Asset Turnover and Capital Structure on Return on Investment - Zakaria Zakaria; Yaya Sonjaya (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study aimed to assess the impact of working capital turnover, asset turnover, and capital structure on manufacturing companies' return on investment (ROI) listed on the Indonesia Stock Exchange. The present study employed a sample of 19 businesses, encompassing 95 observations of manufacturing companies listed on the Indonesia Stock Exchange, spanning 2017 to 2021. The study utilized secondary data from financial statements from sample companies from 2017 to 2021. These data were sourced through prospectuses and the Indonesian Capital Market Directory (ICMD). The method used to look at the data is a descriptive statistical test that includes several standard assumption tests, such as normality, heteroscedasticity, multicollinearity, autocorrelation, and hypothesis testing using partial, simultaneous, and determination coefficient tests. The study's findings indicate no statistically significant impact of the working capital turnover and asset turnover factors on the return on investment (ROI) of manufacturing companies listed on the Indonesia Stock Exchange. On the other hand, the capital structure variable exhibits a substantial influence and emerges as the predominant factor influencing the return on investment (ROI) of manufacturing firms publicly traded on the Indonesia Stock Exchange.